A prospective study of the utility of a routine 'loopogram' at three months for the early detection of anastomotic stricture post-cystectomy and conduit urinary diversion. (November 2018) - Omar, Kawa; Gan, Christine; Rottenberg, Giles; O'Brien, Timothy S; Thomas, Kay; Thurairaja, Ramesh; Khan, Muhammad Shamim
Objective: The objective of this study is to evaluate the utility of routine loopogram follow-up three months after cystectomy and urinary diversion in the early detection of benign ureteroileal anastomotic stricture (UAS). Materials and methods: A loopogram was incorporated into our standard follow-up three months after cystectomy and conduit urinary diversion in August 2010–December 2015. Data were maintained prospectively in a database. Results: A total of 250 patients (181 male; 69 female); median age of 70 years (range: 38–83) underwent cystectomy and conduit urinary diversion during this period. Of these, 167 (66.8%) had a routine loopogram at three months. Seven of 167 were confirmed to have a benign UAS. Twenty-three of 250 (9.2%) had an early loopogram prior to the planned three-month study in response to symptoms. Nine of 23 were diagnosed with benign UAS. Sixty of 250 (24%) did not have a routine loopogram for a variety of reasons. Five patients with normal three-month loopograms developed late strictures after a median time of 22 months (range 5–38). In total 21/250 (8.4%) patients developed UAS. Stricture rates for the open, robotic and laparoscopic modalities were 8/129 (6.2%), 12/111 (10.8%) and 1/10 (10%) respectively. Five of seven of patients with early, asymptomatic UAS diagnosed on routine loopogram received treatment; four of five had improvement in renal function. Conclusion: Overall stricture rate in this series was 8.4%. The majority of UAS occur early and are more likely to be symptomatic. A policy of routine loopogram benefitted only 4/250 (1.6%) patients. We advocate the use of loopograms in cases with a high index of suspicion rather than for routine screening. Level of evidence: Not applicable for this multicentre audit.